2002
DOI: 10.1007/s005350200096
|View full text |Cite
|
Sign up to set email alerts
|

Color Doppler findings of gastric varices compared with findings on computed tomography

Abstract: Although color Doppler sonography is a useful, noninvasive modality for evaluating the hemodynamics of gastric varices, it falls short in visualizing the detailed hemodynamics of the inflowing and outflowing vessels of gastric varices in half of the patients when compared with computed tomography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Komatsuda et al reported the usefulness of CDU for the diagnosis of gastric and duodenal varices, 17 and we concluded that CDU was useful for evaluating of gastric varices. 18 There has been only one report of the diagnosis of rectal varices by CDU. 6 CDU can be performed simply, non-invasively and repeatedly before and after treatments of rectal varices.…”
Section: R Ectal Varices Have Been Reported To Occurmentioning
confidence: 99%
“…Komatsuda et al reported the usefulness of CDU for the diagnosis of gastric and duodenal varices, 17 and we concluded that CDU was useful for evaluating of gastric varices. 18 There has been only one report of the diagnosis of rectal varices by CDU. 6 CDU can be performed simply, non-invasively and repeatedly before and after treatments of rectal varices.…”
Section: R Ectal Varices Have Been Reported To Occurmentioning
confidence: 99%
“…Sato et al [7] in Japan reported that the rates of detection of gastric varices, feeding vessels, and draining vessels with color Doppler in comparison with CT were 100 % vs. 100 %, 87.5 % vs. 100 %, and 75 % vs. 87.5 %, respectively. Color Doppler was not a good modality in comparison with CT for detecting inflowing and outflowing vessels from gastric varices.…”
Section: Imagingmentioning
confidence: 99%
“…ECDUS is useful for detecting rectal varices through color flow images, and it is a necessary tool for effective and safe EIS by calculating the velocity of blood flow in rectal varices (Fig.2). (20). CDUS cannot be performed successfully without a suitable acoustic window.…”
Section: Diagnosis Of Rectal Varices Via Endoscopic Ultrasonography (mentioning
confidence: 99%